Legal Protection for People with Mental Disabilities and the Responsibilities of Notaries After Constitutional Court Decision Number 93/Puu-Xx/2022 - Indria Putri Dinanti (Journal of Comprehensive Science, 2026)
Legal protection for persons with mental disabilities constitutes an important part of the fulfillment of human rights guaranteed by the Indonesian Constitution. However, the provision in Article 433 of the Civil Code previously required individuals with mental disorders to be placed under guardianship (curatele), which potentially removed their legal capacity automatically. This condition created inconsistencies with the principle of non-discrimination and the Convention on the Rights of Persons with Disabilities (CRPD) ratified by Indonesia. This study aims to analyze the juridical implications of the Constitutional Court Decision Number 93/PUU-XX/2022 on the recognition of the legal capacity of persons with mental disabilities and the responsibilities of notaries in civil law practice. The research employed normative legal research using statutory, case, and conceptual approaches. Data were collected through literature study of primary and secondary legal materials and analyzed qualitatively using deductive reasoning. The results show that the Constitutional Court decision transformed the concept of guardianship from a mandatory requirement into an optional protection mechanism. Consequently, persons with mental disabilities are no longer automatically considered legally incapable. The decision also increases the responsibility of notaries to assess the legal competence of parties more substantively through a supported decision-making approach. Therefore, the ruling strengthens the protection of the human rights of persons with disabilities while simultaneously requiring greater prudence in civil law practice and in the drafting of authentic deeds.